2018
DOI: 10.3389/fncir.2018.00079
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Information Flow Based on EEG and Diffusion MRI in Stroke: A Proof-of-Principle Study

Abstract: In hemiparetic stroke, functional recovery of paretic limb may occur with the reorganization of neural networks in the brain. Neuroimaging techniques, such as magnetic resonance imaging (MRI), have a high spatial resolution which can be used to reveal anatomical changes in the brain following a stroke. However, low temporal resolution of MRI provides less insight of dynamic changes of brain activity. In contrast, electro-neurophysiological techniques, such as electroencephalography (EEG), have an excellent tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 73 publications
3
14
0
Order By: Relevance
“…Indeed, preliminary evidence has shown that sensory information travels from the contralateral somatosensory cortex to the ipsilateral somatosensory cortex via the corpus callosum post‐stroke (Filatova et al . 2018). Additionally, sensory recovery post‐stroke has been associated with changes in both the contralateral and ipsilateral somatosensory cortex (Dechaumont‐Palacin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, preliminary evidence has shown that sensory information travels from the contralateral somatosensory cortex to the ipsilateral somatosensory cortex via the corpus callosum post‐stroke (Filatova et al . 2018). Additionally, sensory recovery post‐stroke has been associated with changes in both the contralateral and ipsilateral somatosensory cortex (Dechaumont‐Palacin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, VBMEG was extended to perform a connectome dynamics estimation proposed by Fukushima et al (2015), and its second version was released in 2017. Its usefulness was also confirmed by Filatova et al (2018).…”
Section: Introductionmentioning
confidence: 54%
“…Without assuming region of interests (ROIs), it estimates a whole-brain linear dynamics model by only assuming connectivity coefficients between anatomically connected regions. This drastically reduces the connectivity coefficients to estimate and suppress false positive connectivities (Filatova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During the supervised training, the inverse dynamics moment is used as the target value of the training samples. The variance accounted for (VAF) [51] is used to evaluate the accuracy of the ELM, its expression is as follows:…”
Section: Prediction Evaluationmentioning
confidence: 99%